2006
DOI: 10.1158/0008-5472.can-05-3003
|View full text |Cite
|
Sign up to set email alerts
|

The Forkhead Box m1 Transcription Factor Stimulates the Proliferation of Tumor Cells during Development of Lung Cancer

Abstract: The proliferation-specific Forkhead Box m1 (Foxm1 or Foxm1b) transcription factor (previously called HFH-11B, Trident, Win, or MPP2) regulates expression of cell cycle genes essential for progression into DNA replication and mitosis. Expression of Foxm1 is found in a variety of distinct human cancers including hepatocellular carcinomas, intrahepatic cholangiocarcinomas, basal cell carcinomas, ductal breast carcinomas, and anaplastic astrocytomas and glioblastomas. In this study, we show that human Foxm1 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
268
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 307 publications
(285 citation statements)
references
References 41 publications
11
268
0
4
Order By: Relevance
“…Consistent with an important role of Foxm1 in cell cycle progression, increased expression of Foxm1 was found in human lung adenocarcinomas and squamous cell carcinomas (Kim et al, 2006), prostate adenocarcinomas , basal cell carcinomas (Teh et al, 2002), intrahepatic cholangiocarcinomas (Obama et al, 2005), anaplastic astrocytomas and glioblastomas (van den Boom et al, 2003), infiltrating ductal breast carcinomas (Wonsey and Follettie, 2005), as well as in many other solid tumors (Pilarsky et al, 2004). Foxm1 is also overexpressed in hepatocellular carcinomas from patients who respond poorly to treatment (Lee et al, 2004).…”
Section: Introductionsupporting
confidence: 64%
See 4 more Smart Citations
“…Consistent with an important role of Foxm1 in cell cycle progression, increased expression of Foxm1 was found in human lung adenocarcinomas and squamous cell carcinomas (Kim et al, 2006), prostate adenocarcinomas , basal cell carcinomas (Teh et al, 2002), intrahepatic cholangiocarcinomas (Obama et al, 2005), anaplastic astrocytomas and glioblastomas (van den Boom et al, 2003), infiltrating ductal breast carcinomas (Wonsey and Follettie, 2005), as well as in many other solid tumors (Pilarsky et al, 2004). Foxm1 is also overexpressed in hepatocellular carcinomas from patients who respond poorly to treatment (Lee et al, 2004).…”
Section: Introductionsupporting
confidence: 64%
“…Ubiquitous expression of Foxm1 transgene increases the total number and size of lung tumors induced by MCA/BHT treatment We previously demonstrated that Foxm1 protein is abundantly expressed in highly proliferative human NSCLC as well as in mouse lung tumors induced by urethane (Kim et al, 2006). To determine consequences of Foxm1 overexpression during formation of lung tumors, we used Rosa26-Foxm1 transgenic mice, which contain high levels of Foxm1 protein in all tissues (Kalinichenko et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations